2021
DOI: 10.3390/molecules26185474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Storage on Radical Scavenging Properties and Phenolic Content of Kombucha from Black Tea

Abstract: Kombucha is a fermented beverage. Its consumption has significantly increased during the last decades due to its perceived beneficial effects. For this reason, it has become a highly commercialized drink that is produced industrially. However, kombucha is still also a homemade beverage, and the parameters which, besides its organoleptic characteristics, define the duration of its potential beneficial properties over time, are poorly known. Therefore, this study aimed to determine the effect of 9-month storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 31 publications
1
23
0
1
Order By: Relevance
“…It is therefore possible that other tea polyphenols we did not measure, such as theoflavines, theobromines and gallates [ 44 ], are important contributors to the total antioxidant capacity. Storage conditions after initial production may have also affected the observed profiles, as it has been recently demonstrated that refrigeration of homemade kombucha for longer than 4 months results in reduced polyphenol content and antioxidant properties [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that other tea polyphenols we did not measure, such as theoflavines, theobromines and gallates [ 44 ], are important contributors to the total antioxidant capacity. Storage conditions after initial production may have also affected the observed profiles, as it has been recently demonstrated that refrigeration of homemade kombucha for longer than 4 months results in reduced polyphenol content and antioxidant properties [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total flavonoid content (TFC) was determined using a colorimetric assay method [ 20 ]. Briefly, 300 µL of extract solution (1 mg mL −1 DMSO) dissolved in 900 µL of methanol was mixed with 60 µL of sodium acetate solution (1 M) and 60 µL of 10% aluminium chloride solution and 1.68 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the antioxidant activity and health-promoting properties can be significantly reduced. Latest research results obtained by La Torre et al (2021) show that after four months storage of black tea Kombucha tea at refrigerator, the phenolic content decreased significantly from the initial value of 234.1 ± 1.4 µgGAE/mL to 202.9 ± 2.1 µgGAE/mL, while pH increased from 2.82 to 3.16 [121]. However, it should be remembered that the effect of changes in the profiles of bioactive compounds and the decrease in antioxidant activity are the result of, among others, the activity of microorganisms.…”
Section: The Effect Of Storagementioning
confidence: 99%